Patterned colouring via stretching and heating - Tan, Leonard Jing Zhi (Nanyang Technological University, 2023)
The main focus of this investigation is to utilize both thermal treatment and thermal mechanical treatment to investigate the possibility of producing patterned color and shape memory effects in Polyethylene Terephthalate (PET). Several experiments were carried out to examine PET's properties, including its degree of crystallization and crystallinity, when exposed to different thermal mechanical techniques.